Incidence of Environmental, Social and Emotional Conditions on the Learning of Primary School Students in Rural Areas - Miryan Teresa Mendoza Meza (LÍNEA IMAGINARIA, 2025)
Recognizing the incidence of environmental, social and emotional conditions in the learning of elementary school students in rural areas has an intrinsic value. This objective is to explain how appropriate school environments provide the conditions for students to feel motivated, while identifying those social factors associated with the learning process in the classroom, their elements and characteristics. With these environmental and social conditions, the emotional factors play a very important role that make possible the creation of special classroom learning climates in which the relationship, the interaction with the environment, the identification of the learning experiences themselves come together to give meaning to the educational fact from the valuation of the importance of the creation of environmental, social and emotional conditions for learning in elementary school children in rural schools to be effective and pleasurable. The epistemological approaches proposed by authors such as Goleman, Bisquerra and Vygotsky illuminate the pedagogical perspective from which the learning phenomenon is appreciated and its direct relationship with environmental factors, especially those oriented to the recognition of the value of emotion management and its importance in learning, in addition to other factors that are part of the contextual reality of the elementary school student in the rural area.